Case Report: Giant uterine broad ligament fibroid - Qian, Weiwei; Sheng, Shaoqin; Xu, Xiangqian; Miao, Jiaxin; Nong, Yanying (Frontiers in Oncology, 2026)
Giant uterine fibroids that arise shortly after cesarean section are a rare and distinctive clinical entity. In this research, a retrospective analysis was carried out on the clinical data of a particular patient with such giant uterine fibroids who was admitted to Hangzhou Obstetrics and Gynecology Hospital. What made this case remarkable was that the patient quickly developed symptoms of pelvic and abdominal compression in the period following cesarean section. Imaging examinations disclosed a giant tumor located in the right broad ligament area. Moreover, there was extensive adhesion among the surrounding tissues and the anatomical structure was in disarray, which underlined the complexity of the condition. During the surgical treatment process, a combination of sharp separation and blunt dissection techniques was utilized. In addition, precise management of blood vessels and strategies for protecting important organs were also implemented. Ultimately, the tumor was successfully and completely removed. Postoperative pathology results confirmed that it was a uterine leiomyoma with edematous degeneration. The patient recovered smoothly after the surgery without experiencing any serious complications. Furthermore, no recurrence of the tumor was noticed during the follow-up period. In general, given the rarity, rapid progression, and intricate anatomical connections of giant uterine fibroids after cesarean section, it is of crucial importance to conduct preoperative multimodal imaging evaluations. These evaluations can help clarify the scope of the tumor as well as its adjacent relationships. Besides, during the operation, attaching great importance to adhesion separation techniques and taking good care of important blood vessels and organs, along with the implementation of individualized surgical plans, can remarkably improve the safety and effectiveness of the treatment for these tough and uncommon cases. Meanwhile, taking the clinical diagnosis and management of pregnancy complicated with giant broad ligament fibroids as an entry point, this study systematically demonstrates the clinical advantages and technical feasibility of concurrent myomectomy during cesarean section through the analysis of surgical strategies, operational details, and long-term follow-up data of a typical case. It is intended to provide evidence-based references for individualized clinical decision-making in similar cases.